Tailoring Fe₂O₃-Al₂2O₃ catalyst structure and activity via hydrothermal synthesis for carbon nanotubes and hydrogen production from polyolefin plastics - Veksha, Andrei (2022)
Fe2O3-Al2O3 catalysts applied for conversion of polyolefin plastic waste into multi-walled carbon nanotubes (MWCNTs) and H2 are typically produced by impregnation, co-precipitation or sol-gel synthesis at atmospheric pressure and temperatures below 100 °C. This study utilized hydrothermal conditions and established the role of precipitating agents (urea, N-methylurea and N,N'-dimethylurea) on properties and catalytic activity of Fe2O3-Al2O3 catalysts (Fe-u, Fe-mu and Fe-dmu, respectively). The precipitating agent played a key role in tailoring the properties, such as crystallization degree, surface area and reducibility. The precipitating agents influenced the yield and outer diameters of MWCNTs but did not affect graphitization degree. Among the synthesized catalysts, Fe-u had the largest surface area and preferential formation of the highly reducible α-Fe2O3 crystalline phase. As a result, Fe-u had the highest activity during conversion of pyrolysis gas from low-density polyethylene (LDPE) into MWCNTs, yielding 0.91 g·g-1-catalyst MWCNTs at 800 °C as compared to 0.42 and 0.14 g·g-1-catalyst using Fe-dmu and Fe-mu, respectively. Fe-dmu favored the growth of MWCNTs with smaller outer diameters. Fe-u demonstrated high efficiency during operation using a continuous flow of pyrolysis gas from a mixture of polyolefins (70 wt% polypropylene, 6 wt% LDPE and 24 wt% high density polyethylene) producing 4.28 g·g-1-catalyst MWCNTs at 3.2% plastic conversion efficiency and a stable H2 flow for 155 min (25-32 vol%). The obtained data demonstrate that the selection of an appropriate precipitating agent for hydrothermal synthesis allows for the production of highly active Fe2O3-Al2O3 catalysts for the upcycling of polyolefin plastic waste into MWCNTs and H2.